2020
DOI: 10.15407/microbiolj82.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Vanadium and Germanium Nanoaquacitrates in vitro and their Physiological Effect on Wheat Plants in vivo

Abstract: Phytopathogenic bacteria and phytoplasmas, in particular Pseudomonas syringae pv. atrofaciens and Acholeplasma laidlawii var. granulum are causative agents of cereal crops diseases. Nanoparticles and biologically active compounds created with the use of nanotechnologies are considered as alternative modern measures to control phytopathogenic microorganisms. Antimicrobial activity is already established for gold, silver, copper, magnesium, iron, zinc, aluminum, cerium, titanium, cadmium, nickel and vanadium. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, in our previous studies, the antimicrobial effect of V, Ge, I-Se nanoparticles was shown (Huliaieva H.B. et al, 2020).…”
Section: Resultsmentioning
confidence: 64%
“…On the other hand, in our previous studies, the antimicrobial effect of V, Ge, I-Se nanoparticles was shown (Huliaieva H.B. et al, 2020).…”
Section: Resultsmentioning
confidence: 64%
“…The method of chlorophyll a fluorescence induction (CFI) is an important diagnostic tool in biological research, which reflects the influence of biotic and abiotic factors on the plant and its tolerance to stress (Lichtenthaler et al, 2007;Misra et al, 2012, Maxwell & Johnson, 2000Rahimzadeh-Bajgiran et al, 2017;Stirbet et al, 2018;Guidi et al, 2019;McAusland et al, 2019;Zavafer et al, 2020;Huliaieva et al, 2018;Huliaieva et al, 2020a). First, we focused on determining changes in the F v /F m parameter is the maximum quantum yield of PSII.…”
Section: Figure 1 Appearance Of Symptomsmentioning
confidence: 99%